5-HTTLPR/rs25531 polymorphism and neuroticism are linked by resting state functional connectivity of amygdala and fusiform gyrus - Kruschwitz, Johann; Rietschel, Marcella; Meyer-Lindenberg, Andreas (Brain structure & function, 2014)
The s/s-genotype of the 5-HTTLPR polymorphism and the personality trait of neuroticism have both been associated with experiences of negative affect, anxiety and mood disorders, as well as an emotional processing bias towards negative facial emotions. On a neural level, this bias can be characterized by altered amygdala and fusiform gyrus (FFG) activity during perception of negative facial expressions. Using resting-state functional magnetic resonance imaging in a multi-center-sample of 178 healthy subjects of European descent, this study investigated the association of 5-HTTLPR (short s- and long l-allele) including the genotype of the single nucleotide polymorphism (SNP) rs25531 (A/G) within this region polymorphism, and trait neuroticism on resting-state functional connectivity (rs-FC) between amygdala and the FFG. Moreover, we aimed to identify additional brain regions with associations of 5-HTTLPR/rs25531 (combined according to its expression; low: s/s; high: lA/lA; intermediate: s/lA, s/lG, lG/lG, lA/lG) and trait neuroticism to amygdala rs-FC. Separate analyses for 5-HTTLPR/rs25531 and neuroticism (controlling for age, gender, handedness, and research site) revealed that s/s-homozygotes and individuals high in neuroticism obtained altered amygdala rs-FC in the right occipital face area, which is considered to be a “core component” of the face processing system. Importantly, effects of neuroticism were replicated across three independent research sites. Additionally, associations of 5-HTTLPR/rs25531 genotype and amygdala rs-FC were observed in the anterior and posterior cingulate cortex, whereas neuroticism was not related to rs-FC in these areas. The presented data implies that 5-HTTLPR/rs25531 variants and neuroticism are linked by resting state functional connectivity of amygdala and fusiform gyrus and suggests that variants of 5-HTTLPR/rs25531 genotype and different levels of neuroticism may partly account for altered processing of negative facial emotions.